Polemics on Philosophy: A Comparison of The Thoughts of Al-Ghazāli and Ibn Taymiyyah - Nafiu Ahmed Arikewuyo (Lembaga Kajian dan Pengembangan Sumberdaya Manusia, 2022)
Philosophy is one of the most pressing matters that have polarized the views of Muslim scholars. Among Muslim scholars who’s contributed to the philosophical discourse and left an indelible mark on the thought of subsequent Muslims across the globe; Al-Ghazāli (d.1111C.E.) and Ibn Taymiyyah (d.1328C.E.) are very prominent. Hence, this work is an attempt to compare the views of the two scholars on Philosophy. The study adopts an analytical method. The findings of the study reveal that there is no controversy between the two scholars and even among the generality of Muslim theologians over the impropriety of Peripatetic and Neo-Platonic versions of Philosophy which were the areas of interest of the so-called Muslim Philosophers in the medieval era; the approach adopted in refuting them remains the area of contention between the two scholars. Despite his reputable criticism of the Philosophers, Al-Ghazāli has also been accused by some Muslim theologians of being tainted with some philosophical heresies, while Ibn Taymiyyah, although not like that of the former, has also been alleged of some philosophical influences. The major contribution of the research is the highlight of similarities and dissimilarities between the two scholars vis-à-vis Philosophy